Keefektifan Pelaksanaan Perma No. 12 Tahun 2012 pada Penyelesaian Tindak Pidana Ringan Pencurian Tandan Buah Kelapa Sawit di PT. Masuba Citra Mandiri - Nurhadi, Nurhadi; Hendri, Hendri (Lembaga Yasin AlSys, 2022)
Seeing the rampant theft of tons of palm oil bunches is certainly a special concern for law enforcement in resolving this case. Of course, in terms of justice, if the value of the stolen goods is large while the sanctions given are the same as the theft of a small amount, of course there will be inequality, moreover, whether the category includes weight theft or theft of minor crimes. Therefore, a special study is needed in dealing with this case in order to realize justice and legal order. The issues raised related to the settlement of the occurrence of minor crimes of theft of palm fruit bunches at PT. Masuba Citra Mandiri and obstacles in the Settlement of the Minor Crime of Theft of Palm Fruit Bunches at PT. Masuba Citra Mandiri. This type of research is normative legal research, namely legal research that uses secondary data sources or data obtained through library materials to understand the juridical review of tipiring. The approach method used is the Statute Approach and Conceptual Approach, which is looking for laws and regulations as the initial basis for analyzing and looking for principles, doctrines and sources of law in a juridical philosophical sense as a point of view. view Juridical review of tipir. The effectiveness of implementing Supreme Court Regulation No. 2 of 2012 did not run smoothly. As for the obstacles, namely: law enforcers are not aware of the regulation, law enforcers are more focused on peace not punishment, victims are too well-intentioned so they take the peaceful path, culture of people who like to steal, if they don't have money, people who some have become a habit to commit theft, incitement from friends to participate in the theft of palm fruit bunches, the handling is not serious, socialization to the community in this case providing legal counseling is very minimal, the economy of the surrounding community has not yet reached the point of prosperity, the level of education of the community around PT. MCM is still below SMP.